ЗАМАНАГӨЙ КӨРКЕМ ТӘЛИМДЕ ART-МЕТОДЛАРДАН ПАЙДАЛАНЫЎ ЖОЛЛАРЫ - Уразимова, Т.В.; Исмайлова, А. (ILIM hám JÁMIYET, 2022)
On the basis of the integrated use of the pedagogical potential of various types and means of art, studying the possibility of using the system of art pedagogy, its methods in the educational process, aimed at humanizing the educational environment, optimizing pedagogical interaction, and creative self-realization of subjects of vocational education.